The European Union takes its first steps in regulating the relationship between Artificial Intelligence and Intellectual Property - Moreno, Guillermo Palao (Revista Rede de Direito Digital, Intelectual & Sociedade, 2023)
The “Fourth Industrial Revolution” has meant a ma-jor boost for Artificial Intelligence. Among its multiple implications from a legal perspective, its impact on the management and protection of intellectual property ri-ghts stands out. Faced with this reality, the European Union (EU) has adopted an active stance in mana-ging these relationships. This paper stems from this complicated reality, to address the different initiatives originated in the EU in this field. Not only to expose the underlying objectives and achievements, but also to present the lines that guide their work and future prospects.